(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The article describes the clinical and genetic features of juvenile rheumatoid arthritis and the consequences of the disease after treatment with chronotherapy. The clinical features of the disease, the results of laboratory analysis are important when choosing an effective treatment method. An effective treatment method is characterized by a faster onset of remission, an extension of its duration and a decrease in the side effects of drug treatment. The benefits of breastfeeding for babies are well known, but there is growing evidence that breastfeeding has a positive impact on a mom's health as well. Research shows that breastfeeding lowers a risk for juvenile rheumatoid arthritis.